Societal security: a new conceptual framework to anaylse ultra-orthodox (Haredi) politics in Israel - BELDER, FERİT (My University, 2023)
Haredi (ultra-orthodox) political parties in Israel, namely Yahadut HaTora and Shas, have been constantly affecting the domestic political agenda. Despite already flourished literature that covers the various roles these parties play; security dimension is yet to be addressed so far. This paper aims to analyse the Haredi politics in Israel in the identity-security nexus by questioning the political reflections of the Haredi parties’ persistent attachments to the security language in four core topics which are the Haredi educational autonomy, the exemption of religious school (yeshiva) students from the army service, the conversion to Judaism process (giyur), and the nationwide Shabbat regulations. By analysing the coalition documents that Haredi parties took part in, campaign posters of the 2013 and the 2015 elections, individual and institutional Haredi responses to certain crises regarding these topics, this paper claims that Haredi politics is organized by the articulation of identity-security concerns at varied levels.

İsrail’deki Haredi (ultra-Ortodoks) siyasi partiler, Yahadut HaTora ve Şas, iç siyasi gündemi sık sık etkilemektedir. Her ne kadar bu partilerin oynadığı roller üzerinde gelişmiş bir literatür oluşmuşsa da henüz güvenlik boyutuna işaret edilmemiştir. Bu çalışma, İsrail’deki Haredi (ultra-Ortodoks) siyaseti, Haredi eğitim özerkliği, dini okul (Yeşiva) öğrencilerinin askerlik hizmetinden muafiyetleri, Yahudiliğe geçiş süreci (giyur) ve ulusal ölçekte Şabat düzenlemeleri olmak üzere dört konuda güvenlik diline sürekli bağlılıklarının siyasi yansımalarını sorgulayarak kimlik-güvenlik ekseninde analiz etmektedir. Makale, Haredi partilerin dahil oldukları koalisyon belgeleri, 2013 ve 2015 seçim afişleri ve bu başlıklarda ortaya çıkan krizlere verilen bireysel ve kurumsal Haredi tepkileri analiz ederek Haredi siyasetinin çeşitli düzeylerde kimlik-güvenlik endişelerinin ifadesi ile organize edildiğini iddia etmektedir.
Toplumsal güvenlik: İsrail’de ultra-ortodoks (Haredi) siyaseti analiz etmek için yeni bir kavramsal çerçeve
Keywords: Ultra-Orthodox; Shas; Yahadut HaTora; Societal security; Identity; Ultra-Ortodoks; Şas; Toplumsal güvenlik; Kimlik